PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT MEAD JOHNSON INDONESIA- CABANG BANJARBARU - rakhmi ridhawati; Wahyuni Tri Utami (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
His research aims to empirically proved the influence of compensation and work motivation on employee performance at PT Mead Johnson Indonesia- Banjarbaru branch. The research method used quantitative method, and data collection is carried out through questionnaires distributed directly to respondents with a total of 95 employees from several parts of the company. This study used statistical analysis tools SPSS 26.00 software. The results of the study indicated that compensation has a negative effect on employee performance at PT Mead Johnson Indonesia- Banjarbaru branch, while work motivation does not affect employee performance at PT Mead Johnson Indonesia- Banjarbaru branch. The adjusted R square value is 0.767, which indicates that the dependent variable, namely employee performance, can affect the independent variables, namely compensation and work motivation by 76.7% and the remaining 23.3% is influenced by other variables not mentioned in this study